Potent Anti-Diabetic Activity of Polymeric Microsphere Formulated Metformin on Streptozotocin-Induced Diabetic Rat Model: Pharmaceutical Science-Pharmacology - Kumar Chakra, Biplab; Debnath, Souvik; Mukherjee, Avinaba; Kuotsu, Ketousetou; Chakraborty, Mayur; Kumar Chatterjee, Tapan (International Journal of Life Science and Pharma Research, 2022)
Metformin is an extensively used drug as frontline medicine for type II diabetes. However, the target-specific delivery and efficacy of Metformin in a microsphere formulated pattern has not been studied in detail so far. Therefore, the present study is aimed to develop an oral site-specific rate-controlled anti-diabetic drug delivery system to pacify systemic side effects and offer effective and safe therapy for diabetic diseases with the compressed dose duration of treatment. To formulate this, guar gum and sodium alginate was used, whereas ethyl cellulose was applied as a coating polymer. Subsequent drug entrapment efficiency (DEE) and drug release were performed which indicates the proper formulation and sustained release of Metformin in a microsphere. Thereafter, the formulated drug was applied in Streptozotocin-induced diabetic Swiss albino rats. Histopathology of the liver, kidney, and pancreas was performed. Also, the level of liver glycogen, Glucose-6-phosphate, dehydrogenase, succinate dehydrogenase, and malate dehydrogenase content were significant (* p<0.05, **p<0.01, ***p<0.001) with the metformin-loaded microsphere treated group. Moreover, the drug release from the optimized microsphere at 12 hr was found to be 72%. The significant control in blood glucose and inclined body weight, food, and water intake showed the potential of the formulated drug. A similar range of VLDL and the other lipid profile, especially HDL level, offers the combined metformin-loaded microsphere reversal effect on cholesterol and cardiovascular risk. Overall, this study depicts, the significant antidiabetic efficacy of metformin's polymeric microsphere using natural guar gum which can improve the blood glucose level, lipid profile level, and histopathological architecture of concerned organs. ; ;; ,